2020
DOI: 10.1088/2053-1583/abbac1
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of AgxTaS2 superconductor with stage-3 structure

Abstract: Through interfacial engineering, such as ion intercalation, we can tune the properties and optimize the performance of transition metal dichalcogenides and their devices. In this study, we present the first-time experimental investigations of stage 3 of AgxTaS2 single crystal, and its superconductivity was discovered at 3.8 K. Highly crystalline stage 1 and 2 were prepared by a proton-driven ion-introduction method. A simple water-soaking process was employed to achieve the stage-3 structure by deintercalation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…The interactions between Ag ions in TMDs (TiS 2 , TaS 2 , and NbSe 2 ) with the 2D structure were investigated via DFT calculations; it has been reported that these intercalation compounds can be synthesized experimentally. [ 5,7b,21 ] When Ag ions were the farthest away from each other, the most stable state could be obtained in TMDs (Figures S16 and S17b,c,e, Supporting Information). Thus, the attraction between cations in ZrTe 3 is unusual among intercalation compounds.…”
Section: Mechanism Forming the Quasi‐amorphous Phasementioning
confidence: 99%
See 1 more Smart Citation
“…The interactions between Ag ions in TMDs (TiS 2 , TaS 2 , and NbSe 2 ) with the 2D structure were investigated via DFT calculations; it has been reported that these intercalation compounds can be synthesized experimentally. [ 5,7b,21 ] When Ag ions were the farthest away from each other, the most stable state could be obtained in TMDs (Figures S16 and S17b,c,e, Supporting Information). Thus, the attraction between cations in ZrTe 3 is unusual among intercalation compounds.…”
Section: Mechanism Forming the Quasi‐amorphous Phasementioning
confidence: 99%
“…However, unlike the 2D layered compounds, structural changes in TMT intercalation compounds cannot be comprehended by the simple expansion of the lattice constant. [ 5 ] Structural analysis is the most challenging issue in treating the TMT intercalation compounds because the intercalation into three‐dimensionally spread van der Waals gaps induces flexible structural changes and reduces the crystallinity. Elucidating the crystal structure of TMT compounds after the intercalation process is one of the critical topics in this family.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, ion exchange, , introduction, , and extraction are also effective for synthesizing metastable materials. These reactions can be applicable in materials with a large difference in chemical bond strength between constituent elements. , If the diffusion of weakly bonded ions can be controlled while maintaining the basic crystal structure, a metastable phase, which cannot be obtained by simple heat treatment, would be formed, and the electron carrier density would be tuned by modulating the elemental composition .…”
Section: Introductionmentioning
confidence: 99%
“…Such a deteriorated intergrain contact significantly suppresses the ion diffusion flow. Therefore, the synthesis using anisotropic ion diffusion is effective for materials such as glass that flexibly change shape at high temperatures, soft layered single crystals stacked by the van der Waals force, ,,, and substances with a structure whose volume hardly changes with ion introduction and extraction like zeolite.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation